Quadrinhos para quadrinhos: metalinguagem na realização de material didático para a criação de HQs nas aulas de arte do ensino fundamental II - Sousa, Osvaldo Araújo de (2023)
This article discusses the importance of using comics in Elementary School Art classes II from a question: Is it possible to develop an approach that is, for students, expressive and relevant when working with comics? Starting from the relevance that comics represent as an artistic language and in the educational proposal, a research was carried out based on a qualitative phenomenological methodology, developing a didactic material aimed at Art classes in Elementary School II, with the intention of bringing a possible proposal to students. teachers and that it is positive for the students, adding knowledge to the content, with different applied practices. There is a description of a brief history of comics and their relationship with education, pointing out the use of comics in the classroom and the changes that have occurred over the years and some basic elements of a comic book are exposed, culminating in the proposal of didactic material aimed at practice in Art classes. The research began during the Covid-19 pandemic. Therefore, it was thought to bring a material that can be applied in both face-to-face and virtual environments. Some of the results obtained were through practical productions of the students, realizing the development of skills and the assimilation of content, as well as the interaction of the students with the proposal of becoming protagonists, with a feeling of representativeness, proving, therefore, the relevance of the research , showing that it is indeed possible to significantly develop an approach to comics with students.